Implementasi Manajemen Supervisi Klinis Dalam Mengembangkan Kompetensi Pedagogik Guru - Kusrinisari; Ahmad Thohirin; M. Furqon Wahyudi (MAN Insan Cendekia Jambi, 2026)
This study aims to describe the implementation of clinical supervision management in developing teachers’ pedagogical competence. Clinical supervision is viewed as a professional development process that focuses on systematic, collaborative, and continuous teacher mentoring. This study employed a qualitative approach, with data collected through interviews, classroom observations, and document analysis. The research subjects consisted of the school principal and teachers. The results indicate that clinical supervision management was implemented through the stages of planning, implementation, evaluation, and follow-up. The supervision planning was designed flexibly based on teachers’ needs and the dynamics of classroom learning. The implementation of clinical supervision was carried out through pre-observation, observation, and post-observation stages using a reflective dialogue approach. The evaluation process emphasized joint reflection and improvement of the learning process rather than individual performance appraisal. Follow-up programs were conducted through individual mentoring and collaborative activities within the school-based teacher working group (KKG). The implementation of clinical supervision had a positive impact on improving teachers’ pedagogical competence, particularly in lesson planning, learner-centered instructional practices, classroom management, the use of instructional methods and media, and learning assessment.